Concentrating greywater using hollow fiber thin film composite forward osmosis membranes: Fouling and process optimization. (23rd November 2018) - Xiao, Tingting; Dou, Pengjia; Wang, Jin; Song, Jianfeng; Wang, Yanqing; Li, Xue-Mei; He, Tao
Highlights: Greywater was concentrated using TFC forward osmosis membrane up to ten times. Casein and Calcium ions caused severe FO membrane fouling. Osmotic backwash using caustic water recovered the membrane performance. Coagulation using FeCl3 resulted in very stable FO operation. High quality water could be extracted using FO based integral treatment process. Abstract: Greywater is the main source of municipal wastewater, but lightly polluted. This paper reported a novel forward osmosis (FO) for treating the greywater to obtain pure water. The hollow fiber thin film composite (TFC) FO membrane was synthesized and characterized. For the main organic foulants in greywater, the same FO membrane showed higher rejection in a FO operation than in a hydraulic pressure driven reverse osmosis operation. In a systematic analysis of the FO membrane fouling up to a concentration factor of 10, the protein, casein, was identified as the main factor; conjugation with Ca 2+ and SDS accelerated the membrane fouling. Osmotic backwash using caustic solution could effectively recover the FO membrane flux. Moreover, the FO membrane fouling was significantly alleviated after using ferric chloride flocculant as the pretreatment. Water analysis showed that nearly 100% of large organic contaminants such as humic acid, casein, and most of the phosphate ions (below detection limit), were removed by the FO membranes but allowed small amount of SDS and NH4 + to permeate across. The present results provided a scientific and engineering basis for the potential application of forward osmosis membrane based integral process for treating greywater.